2020
DOI: 10.4209/aaqr.2020.04.0176
|View full text |Cite
|
Sign up to set email alerts
|

Fugitive Aerosol Therapy Emissions during Mechanical Ventilation: In Vitro Assessment of the Effect of Tidal Volume and Use of Protective Filters

Ciarraí O’Toole,
James A. McGrath,
Mary Joyce
et al.

Abstract: Background: During mechanical ventilation of a patient requiring ventilatory support bystanders could potentially be exposed to aerosolised drug. Methods: Fugitive drug aerosol emissions during simulated adult mechanical ventilation was assessed on a dual limb circuit. Tidal volume was set at 270 mL and 820 mL. The use of a protective filter on the exhalation port of the mechanical ventilator was assessed. Results: Higher fugitive aerosol mass concentrations in the local environment were associated with larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This study highlights the importance of nebuliser selection as a deciding factor to reduce the risks associated with aerosol therapy during mechanical ventilation. While remaining cognisant of the risks associated with nebuliser selection on the transmission of infection to healthcare workers during drug administration, such as the lack of exhalation limb filtration [26][27][28][29][30], the recommended use of vibrating mesh nebulisers has now been validated.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the importance of nebuliser selection as a deciding factor to reduce the risks associated with aerosol therapy during mechanical ventilation. While remaining cognisant of the risks associated with nebuliser selection on the transmission of infection to healthcare workers during drug administration, such as the lack of exhalation limb filtration [26][27][28][29][30], the recommended use of vibrating mesh nebulisers has now been validated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors noted that up to 45% of the nominal dose placed in the nebulizer could escape. More recently, O'Toole et al [17] suggested that during mechanical ventilation, both tidal volume and filter use have significant influence on the levels of medical aerosol emissions. Using a bag-valve mask, studies by both Hui et al [18] and Chan et al [19] recorded significant exposure risk from bioaerosols to caregivers at distances of up to 0.8 m from a simulated manually ventilated patient.…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 survey by Ehrmann et al [20] found that only 65% of physicians made use of filters during mechanical ventilation, with as many as 28% never changing the filter. Recent reviews and studies point to the importance of filter use and closed-circuit nebulizers and systems, especially in times such as during the COVID-19 pandemic [17,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, and to ensure safe volumes and pressures are delivered to the patient’s lung on each breath, air leak is minimal, with cuffed endotracheal tubes creating a complete seal within the trachea. This again not only facilitates increased aerosol delivery, but also reduces fugitive medical aerosol emissions to the local environment, and, cognizant of COVID−19, the risk of patient derived transmission of infectious disease [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%